2014
DOI: 10.7314/apjcp.2014.15.15.6349
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Promotes Proliferation and Migration of Breast Cancer Cells through the Extracellular Regulated Kinase Pathway

Abstract: The present study was undertaken to determine the roles of insulin in the growth of transplanted breast cancer in nude mice, and the proliferation and migration of MCF-7 human breast cancer cells and assess its influence on downstream signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…MAPK is one of the protein kinases which can be stimulated in many kinds of cancer cells and related to tumorigenesis [10][11][12][13]. Smallmolecule inhibitors targeted MAPK have been wildly used for cancer therapeutics as a biologically viable model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK is one of the protein kinases which can be stimulated in many kinds of cancer cells and related to tumorigenesis [10][11][12][13]. Smallmolecule inhibitors targeted MAPK have been wildly used for cancer therapeutics as a biologically viable model.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ERK1/2 acts as nearly 180 different molecules targets and regulates several diverse cellular functions such as cell growth, cell cycle, proliferation, cell death, cell apoptosis, cell adhesion and transcription [9]. In fact, the ERK1/2 plays the above roles in various cancers, such as breast cancer [10], colorectal cancer [11], prostate cancer [12] and lung cancer [13]. However, not all references support the role of activated ERKs in promoting tumorigenesis, and result consistent with the role in tumor suppression has been reported as well [14].…”
Section: Introductionmentioning
confidence: 99%
“…By binding to IRs, insulin enhances the proliferation and migration of MCF-7 via extracellular signal-regulated kinase (ERK) signaling in vivo and in vitro (14,15). Consistent with this, the present results showed that the level of phosphorylated IRs was increased in MSC-pretreated human breast cancer MDA-MB-231 cells, without significant alteration in the level of phosphorylated insulin-like growth factor 1 receptors (IGF-1Rs) and the subsequent c-Jun N-terminal kinase (JNK) activation, thus enhancing cell proliferative and migratory abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there exist other studies revealing the crosstalk between MLCK and ERK1/2 in the process of cell migration (Zhou et al, 2008). ERK1/2, one of MAPKs signal cascade, is known as a prominent signal pathway in cell proliferation and differentiation (Pan et al, 2014;Zhu et al, 2014a). Whereas the detailed mechanisms of ERK1/2 together with MLCK in cell migration are unclear.…”
Section: Discussionmentioning
confidence: 99%